Critical stages of water requirement in sweet orange (Citrus sinensis) (Current Horticulture, 2024)
A field experiment was conducted on 10-year-old bearing sweet orange (Citrus sinensis Osbeck) cv. Sathgudi based on evaporation replenishment (ER) irrigation scheduling at different stages to identify the critical stage of irrigation water requirement through drip irrigation system during 2007-2017 at AICRP on Fruits (Citrus), Citrus Research Station, Dr Y.S.R Horticultural University, Tirupati. The fruit yield and quality significantly affected under various ER based drip irrigation scheduling treatments. Maximum number of fruits (353 fruits/ plant) and highest fruit yield (57.41 kg/plant and 15.92 t/ha) were recorded under drip irrigation scheduled at 80% ER in all stages. The best quality fruits (TSS:10.270 Brix and acidity 0.71%) with good TSS and acid blend (17.25) and highest benefit: cost ratio (2.68) were harvested in the same treatment and it was superior over all the treatments, indicating stage VI (November-December) is the best period for inducing stress for Ambe bahar crop. However, lowest yields were recorded when plants were supplied with 80% ER at stage I, II, IV, V, VI stages and 30% ER at Stage III (May-June), followed by plants supplied with 80% ER at stage II, III, IV, V and VI stages and 30% ER at stage I (January-February). Reduction in irrigation from 80% ER to 30% ER during stage III (May-June: fruit development stage) and stage I(January-February: flowering and fruit setting) resulted in significant reduction in yield, indicating both the stages are critical for water requirement in sweet orange.
Keywords: Critical stage; Flowering; Fruit setting; Irrigation scheduling; Stress; Sweet orange; Water requirement